Wybrane leksykalne sposoby wyrażania wartości w pismach uczniów szkół średnich - Wrześniewska-Pietrzak, Marta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2009)
The aim of the article is to present characteristic lexical means of expressing values used in secondary school students` compositions between the years 2000 and 2004. The methods of evaluation discussed in the article have been divided into two groups that constitute an example of systemic evaluation (lexemes that evaluate primarily and secondarily) and context evaluation (specifying the meaning of a lexeme, changing the value of a lexeme by context, the phenomenon of evaluation through stereotypes). Moreover, the article points out the devices which can be placed between conventionalised and context means (e.g., multi-evaluating lexemes or proper names referring to the transcendental sphere). The analysis of lexical material enabled researchers to draw a number of conclusions that show a linguistic picture of the world of values present in students` compositions. This picture appears well-ordered and stable. Additionally, it includes all evaluation classes identified in the axiological typology compiled by Jadwiga Puzynina.